2012
DOI: 10.1039/c2sc20628e
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting a dimeric silver transmetallating reagent to synthesize macrocyclic tetracarbene complexes

Abstract: A dimeric macrocyclic tetra-N-heterocyclic carbene (NHC) silver complex was synthesized and shown to successfully extend transmetallation of polydentate NHCs beyond bidentate NHCs. The silver complex was utilized in the preparation of a variety of monomeric tetra-NHC complexes ranging from early first row to late third row transition metals in moderate to high yield for a total of nine examples of transmetallation. Among these complexes are rare examples of silver transmetallation with first row transition met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
83
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(96 citation statements)
references
References 66 publications
13
83
0
Order By: Relevance
“…This preparation shows the successful extension of transmetallation of polydentate NHCs beyond bidentate NHCs. It is an octahedral complex with Cr-C carbene bond lengths in the region of 2.09 and 2.14 Å[178], which are comparable to those in Cr dicarbene complexes. 12 Cr(II) tetra-NHC complex[178].4.1.2.2.3 Cr-NHC complexes containing hybrid NHC ligandIn 2006, Danopoulos et al reported the synthesis of 'pincer' dicarbene complexes Cr-78a and Cr-78b (Figure 4.13), which contain [C-N-C] type ligands.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…This preparation shows the successful extension of transmetallation of polydentate NHCs beyond bidentate NHCs. It is an octahedral complex with Cr-C carbene bond lengths in the region of 2.09 and 2.14 Å[178], which are comparable to those in Cr dicarbene complexes. 12 Cr(II) tetra-NHC complex[178].4.1.2.2.3 Cr-NHC complexes containing hybrid NHC ligandIn 2006, Danopoulos et al reported the synthesis of 'pincer' dicarbene complexes Cr-78a and Cr-78b (Figure 4.13), which contain [C-N-C] type ligands.…”
mentioning
confidence: 88%
“…11 Cr(II)(III) complexes with di-NHC ligands[176].The first tetracarbene Cr complex Cr-77[178] (Figure 4.12) was reported by Jenkins et al in 2012. It was prepared from a transmetallation method with a dinuclear silver complex with macrocyclic tetra-NHC.…”
mentioning
confidence: 95%
“…The first approach utilizes the transmetallation route (Scheme 13) for preparing the (665), [201] (666−667), [202] (675), [203] (676), [161] (677−678), [204] (679), [203] (682), [205] (683), [206] (684−685), [207] (686−687), [208] (689), [209] (690), [210] (691), [211] (692−695), [203] (697−702), [203] (703−706), [212] (707), [213] (708) [214] and (709−710) [215] complexes from the respective Ag(I)−NHC complexes by the treatment with various Ni(II) precursors namely, NiCl 2 (PPh 3 ) 2 , (DME)NiX 2 (X = Cl, Br) and…”
Section: Di-cationic Chelated Ni(ii)−nhc Complexesmentioning
confidence: 99%
“…(200),[91] (201),[92] (202),[93] (203),[91] (204−206),[92] (207) [94] and(208−209) [95] were synthesized by this method from the reaction of nickelocene derivatives and the azolium salts (Scheme 14 andFigure 16).…”
mentioning
confidence: 99%
“…[4][5][6][7][8][9][10] Palladium represents one of the most versatile transition metals utilised for catalysing a multitude of transformations, being applied in the synthesis of polymers, 11 nanocomplexes, 12 liquid crystals 13 and, most commonly, natural products. [14][15][16] Numerous Pd-NHC complexes have been reported, including homoleptic Pd 0 bis-carbene, 17,18 chelating/macrocyclic Pd II carbene 19,20 and mixed carbenephosphine Pd complexes. 21,22 Well-defined Pd-NHCs bearing ancillary nitrogen donor ligands have demonstrated significant activities in both carbon-carbon and carbon-heteroatom crosscoupling reactions.…”
Section: Introductionmentioning
confidence: 99%